PediatricEducation.org (Out of Print) - Donna D'Alessandro (Association of American Medical Colleges, 2006)
Abstract This continuing pediatric education program for residents, fellows, and staff physicians practicing pediatrics aims to broaden and deepen their pediatric knowledge through daily delivery of small-granule pediatric cases that can be integrated into their workflow. Medical students beginning their study of pediatrics or other health care providers practicing pediatrics may also find the program useful. Each case begins with a question, and the case is then used to illustrate and discuss that question, thus creating a form of situated learning focused on the discussion that occurs at a higher level after the diagnosis is made. Over time, these cases will aggregate into an unstructured curriculum of pediatric topics, closely paralleling the structured curriculum of a pediatric residency, fellowship, and continuing medical education program. Engaging in discussions related to these cases will also result in the development of educational collaborative relationships. Qualitative analysis of 100 user-submitted comment forms showed that visitors represented the spectrum of learners, from students to residents and fellows to pediatric health care providers (nurses, nurse practitioners, physicians) and professors in the domains of emergency medicine, family medicine, pathology, pediatrics, and radiology. This resource shows excellent promise for forming an unstructured curriculum of pediatric education based upon coverage of age ranges, pediatric specialties, symptoms, and disease/problems.